THE IMPACT OF INCENTIVE, OCCUPATIONAL SAFETY, AND ORGANIZATIONAL COMMITMENT TOWARDS EMPLOYEE PERFORMANCE DURING THE COVID-19 PANDEMIC - Putra, Ivan Gumilar Sambas; Azmi, Aulia Ulfah; Fadhlillah, Irsalina; Ulfah, Widya; Hasan, Zia (CENTRAL ASIA AND THE CAUCASUS, 2022)
The COVID-19 pandemic makes the employee performance to face harder challenges, especially in several areas such as health, organizational commitment, and the employee incentive. The fear and risk that the employees feel during the pandemic might force them to receive worthy stimuli to maintain their performances. This research used survey on 68 employees of Bank Tabungan Negara to identify incentive variable, occupational safety, and organizational commitment towards the employees during the COVID-19 pandemic. The result od the study showed that the incentive, occupational safety, and organizational commitment influenced positively on the employee performances. It meant that the higher incentive, occupational safety, and organizational commitment were, the better the employees’ performances would be, especially during the pandemic. This study explained that incentive had a consistent impact towards the employee performance. This research indicated that the companies needed to facilitate proper incentive to their employees, that would later make the employees feel comfortable at their work, and then, improving their work qualities. This, in turn, would improve the company. Empirically, the BTN bank gave the variable compensation in a form of long-term compensation (LTI) valued at Rp. 275 billion to their staff. The funds used to buy the stock market in the secondary market. Consistently, the occupational safety impacted the company performance, which was pivotal for the company to implement the occupational safety to improve the employee performance. Empirically, the BTN bank maximized the work from home activity (WFH) to minimize the spread of the virus. This step was taken by the company to anticipate the virus spread without any banking service interruption, also by prioritizing the health and safety of the customers and employees. However, the incentive, occupational safety, and organizational commitment consistently influenced the employee performance. Empirically, the organizational commitment of BTN bank towards the employees were conducted to empower the staff, including the millennial employees, through various steps, such as the performance management, authority & empowerment, resources, training, collaboration, work, structure, and process. This was due to the fact that the employees required a decent wage, insurance, and organizational commitment. Empirically, the BTN bank could afford those three factors, such as distributing incentives, maintaining the occupational safety by optimizing the work at home. The BTN bank could always innovate in developing the employee capabilities.